The influence of foot posture on the cost of transport in humans - Cunningham, C. B.; Schilling, N.; Anders, C.; Carrier, D. R. (The Journal of Experimental Biology, 2009)
Although humans appear to be specialized for endurance running, the plantigrade posture of our feet, in which the heel contacts the substrate at the beginning of a step, seems incompatible with economical running. In this study, we tested the hypothesis that plantigrade foot posture reduces the energetic cost of transport (COT) during walking in humans. When human subjects walked with their heels slightly elevated in a `low-digitigrade` posture, COT increased by 53% above that of normal plantigrade walking. By contrast, there was no difference in COT when subjects ran with digitigrade versus plantigrade foot posture. Stride frequency increased and stride length decreased when subjects switched to digitigrade walking; however, this change did not influence the COT. Additionally, we found that possible reductions in postural stability appear not to have caused the elevated cost of digitigrade walking. Digitigrade walking, however, did (1) increase the external mechanical work performed by the limbs; (2) reduce the pendular exchange of kinetic and potential energy of the center of mass; (3) increase the average ground reaction force moment at the ankle joint; and (4) increase the recruitment of major extensor muscles of the ankle, knee, hip and back. These observations suggest that plantigrade foot posture improves the economy of walking. Relative to other mammals, humans are economical walkers, but not economical runners. Given the great distances hunter-gatherers travel, it is not surprising that humans retained a foot posture, inherited from our more arboreal great ape ancestors, that facilitates economical walking.